2008
DOI: 10.1159/000149586
|View full text |Cite
|
Sign up to set email alerts
|

Renal ACE and ACE2 Expression in Early Diabetic Rats

Abstract: AbstractBackground/Aim: The role of angiotensin-converting enzyme (ACE)-related carboxypeptidase-2 (ACE2) in the regulation of the renin-angiotensin system is not well characterized. This study investigated the changes in the expression of ACE and ACE2 in the kidney in early diabetic rats. Methods: Streptozotocin-induced diabetic rats were examined. The concentrations of angiotensin II in plasma, urine, and renal cortex were measured by radioimmunoassay. The mRNA expression of ACE, ACE2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 71 publications
3
18
1
Order By: Relevance
“…Colocalization of ACE2 and megalin, a PCT marker protein, confirmed this localization of ACE2. The previous studies consistently demonstrated that ACE2 staining in the rat kidney is in the PCT, whereas the results for glomerular staining with anti-ACE2 antibody have varied [18][19][20][21][22]. No glomerular staining of ACE2 was seen in the present study, and the staining was mainly seen on the brush-border membranes.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Colocalization of ACE2 and megalin, a PCT marker protein, confirmed this localization of ACE2. The previous studies consistently demonstrated that ACE2 staining in the rat kidney is in the PCT, whereas the results for glomerular staining with anti-ACE2 antibody have varied [18][19][20][21][22]. No glomerular staining of ACE2 was seen in the present study, and the staining was mainly seen on the brush-border membranes.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, changes in ACE2 expression and activity have been reported in various kidney injury models. ACE2 expression in the tubules of rats with streptozotocininduced diabetes has been found to be decreased [21], and kidney biopsy specimens from diabetic patients have shown decreased expression of tubular and glomerular ACE2 [24]. Spontaneously hypertensive rats also show decreased tubular ACE2 expression when they develop hypertension, whereas glomerular expression of ACE2 increased after birth and after the development of hypertension [19].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on ACE2 expression reported similar results [28,29,30], with the same discordance between protein and mRNA expression. It is therefore possible that ACE2 is altered at the posttranscriptional level not only in diabetic animals [28,29] and human diabetic patients [30], but also in other diseases including IgA nephropathy.…”
Section: Discussionsupporting
confidence: 71%
“…Most groups agree, however, that deletion of ACE2 causes significant potentiation of the effects of ANGII (Yamamoto et al 2006;Epelman et al 2008;Moon et al 2008;Soler et al 2008). Yamamoto and his colleagues recently reported that deletion of ACE2 accelerates pressure overload-induced cardiac dysfunction in mice.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is highly expressed in the endothelial cells of the heart, kidney, and testis, and mainly degrades ANG II to angiotensin 1-7 (ANG 1-7), which is thought to act as a vasodilator and is involved in apoptosis and growth arrest, in contrast to ACE activity which generates ANG II and degrades ANG 1-9 (Epelman et al 2008;Moon et al 2008;Soler et al 2008). Thus, ACE2 might be a potent counter-regulator against ACE and thus play a protective role in many diseases.…”
mentioning
confidence: 99%